Implementation of Higher Order Thinking Skills (HOTS) in Strengthening Character Education Towards Arabic Language Learning - Hayani, Aida; Farhan, Moh.; Assalihee, Muhammadfeefee (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
Nowadays, integrating cognitive skills with moral development is a key concern among educators and policymakers. Strengthening Higher Order Thinking Skills (HOTS) alongside character education is considered vital to cultivate students who are both intellectually capable and morally grounded. This article presents the analysis of the implementation of Higher Order Thinking Skills (HOTS) in strengthening character education within Arabic language learning at Misabul Ulum Paloh Aceh. The research employed a qualitative descriptive approach aimed at capturing naturally occurring educational practices without manipulation. Data were obtained through classroom observations of Arabic language lessons across three grade levels, structured interviews with the school principal, vice principal for curriculum affairs, two Arabic language teachers, and six students, as well as through documentation of lesson plans, assessment instruments, and student learning portfolios. The findings indicated that the integration of HOTS into Arabic language instruction effectively contributes to the development of five core character values promoted by the Ministry of Education and Culture, namely religiosity, integrity, nationalism, independence, and cooperation. The findings showed that integrating HOTS in Arabic learning builds students’ discipline, honesty, and responsibility. This supports Bloom’s and Krathwohl’s theories on cognitive and affective development. Teacher role models and supportive environments strengthened these outcomes, in line with Bandura’s Social Learning Theory. Barriers such as teacher competence and student readiness reflect Vygotsky’s ZPD concept. The study implied that HOTS-based Arabic learning promotes both intellectual and moral growth, highlighting the need for teacher training and supportive learning conditions.